Increasing the Ligand Field Strength in Butadiene Open Sandwich Compounds from the First to the Second Row Transition Metals. Issue 21 (4th June 2020) - Qian, Junfeng; Chen, Qun; He, Mingyang; Zhang, Zhihui; Feng, Xuejun; Xie, Yaoming; King, R. Bruce; Schaefer, Henry F.
Abstract: The structures and energetics of the bis(butadiene) complexes of the second row transition metals (C4 H6 )2 M) M=Zr to Pd) have been investigated by density functional theory. The energetically accessible (C4 H6 )2 M structures (M=Zr to Rh) are found to have only tetrahapto η 4 ‐C4 H6 ligands. The second row transition metals energetically prefer low spin states in their bis(butadiene) derivatives (C4 H6 )2 M reflecting their increased ligand field strength relative to the first row transition metals. Thus the energies of the singlet and doublet spin states for (C4 H6 )2 Ru and (C4 H6 )2 Tc, respectively, are lower than their triplet and quartet spin state isomers in contrast to the corresponding iron and manganese systems, respectively. Furthermore, the staggered maximum spin (C4 H6 )2 M structures with χ ≈ 90° having tetrahedral coordination of the central metal to the four C=C double bonds of the two butadiene ligands found as lowest energy structures for the first row transition metals are not found for the second row transition metals from Mo to Pd. Instead the lowest energy (C4 H6 )2 M structures for the second row transition metals have an eclipsed confirmation with χ ≈ 0° implying square planar coordination of the central metal. The lowest energy structure of the palladium complex (C4 H6 )2 Pd is anomalous since only one of the two butadienes is a tetrahapto ligand whereas the second butadiene is only a dihapto ligand leaving one uncomplexed C=C double bond. Abstract : The second‐row transition metals energetically prefer low spin states in their bis(butadiene) derivatives (C4 H6 )2 M reflecting their increased ligand field strength relative to the first‐row transition metals. Staggered maximum spin (C4 H6 )2 M structures having tetrahedral coordination of the central metal to the four C=C double bonds of the two butadiene ligands are not found.